2-(Naphthalene-2-thio)-5, 8-dimethoxy-1, 4-naphthoquinone induces apoptosis via ROS-mediated MAPK, AKT, and STAT3 signaling pathways in HepG2 human hepatocellular carcinoma cells. (2nd January 2022) - Liu, Yang; Luo, Ying-Hua; Li, Shu-Mei; Shen, Gui-Nan; Wang, Jia-Ru; Zhang, Yi; Feng, Yu-Chao; Xu, Wan-Ting; Zhang, Yu; Zhang, Tong; Xue, Hui; Wang, Hong-Xing; et al.
Abstract: 1, 4-naphthoquinone and its derivatives have attracted widespread attention due to their multiple biological activities, such as induction of cancer cell apoptosis; however, most of these compounds have high cytotoxicity. In this study, in order to reduce their toxicity and increase their potential anti-tumor effects, we synthesized a novel 1, 4-naphthoquinone derivative named 2-(naphthalene-2-thio)-5, 8-dimethoxy-1, 4-naphthoquinone (NTDMNQ), and investigated its apoptotic effects and underlying mechanism. Our results showed that NTDMNQ inhibited the viability of HepG2, Hep3B, and Huh7 human hepatocellular carcinoma (HCC) cells. It also increased the accumulation of cells in the G0/G1 phase of the cell cycle by increasing the expression levels of p-p53, p21 and p27, while decreasing the levels of Cyclin D1, Cyclin E, Cyclin-dependent kinase 2 (CDK2), CDK4, and CDK6. Inhibition of reactive oxygen species (ROS) by the ROS scavenger N-acetyl-L-cysteine (NAC) decreased apoptosis in NTDMNQ-treated cells. Western blot analysis showed that NTDMNQ increased the phosphorylation of p38 and c-Jun N-terminal kinase (JNK), and decreased the phosphorylation of extracellular signal-regulated kinase (ERK), AKT, and signal transducer and activator of transcription-3 (STAT3); these effects were blocked by NAC. Both the JNK inhibitor (SP600125) and p38 inhibitor (SB203580) reversed the phosphorylation of STAT3, and the ERK inhibitor (FR180204) and AKT inhibitor (LY294002) reduced the expression of STAT3. Taken together, these findings suggest that NTDMNQ induces apoptosis via ROS-mediated MAPK, AKT and STAT3 signaling pathways in HepG2 cells, and may be a potent anticancer agent.